The Influence of Fintech Payment Usage, Financial Literacy, and Lifestyle on the Financial Management Behavior - Sabrina Nafishabila; Ariati Anomsari (Golden Ratio of Finance Management, 2026)
This research looks at how lifestyle, financial literacy, and fintech payments affect university students` financial management practices. It aims to identify the extent to which digital payment usage, financial knowledge, and consumption patterns influence students’ ability to manage their finances effectively. A quantitative explanatory technique is used in this research. Purposive sampling was applied to gather data collected from Universitas Dian Nuswantoro Faculty of Economics and Business students. Respondents were given a standardized questionnaire employing a 5-point Likert scale. To assess the correlations between the variables, the data were analyzed through Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method. The findings show that fintech payment, financial literacy, and lifestyle have significant effects on financial management behavior, both partially and simultaneously. Financial literacy shows the strongest influence, while fintech payment and lifestyle also contribute to shaping financial behavior among students. This study presents empirical data on financial behavior, especially with regard to students' use of digital finance. Practically, the findings highlight the importance of strengthening financial literacy and promoting responsible use of digital payment systems to support better financial decision-making.